The Magic Begins: Book 1 (Charm Hall) - Tabitha Black (London Hodder Children's books, 2007)
Paige doesn't want to go to boarding school but once she meets new best friends Summer and Shannon, she never wants to leave Charm Hall. A mysterious black kitten appears in their dormitory. Pets are strictly not allowed at Charm Hall but they don't have the heart to get rid of her, and they name her Velvet. It soon turns out that Velvet is more than an average kitten - there's something magical about her!